Dammarane-Type Triterpenoids from The Stembark of Aglaia argentea (Meliaceae) - Ace Tatang Hidayat; Kindi Farabi; Ida Nur Farida; Kansy Haikal; Nurlelasari Nurlelasari; Desi Harneti Putri Huspa; Rani Maharani; Unang Supratman; Yoshihito Shiono (Jurnal Kimia Valensi, 2018)
Two dammarane-type triterpenoids, 20S,24S-epoxy-3α,25-dihydroxydammarane (1) and 3α-acetyl-20S,24S-epoxy-3α,25-dihydroxydammarane (2), have been isolated from the stembark of Aglaia argentea. The chemical structure of compounds (1 and 2) were identified by spectroscopic evidences including UV, IR, 1D-NMR, 2D-NMR and MS as well as by comparing with previously reported spectral data. Those compounds were isolated from this plant for first time. Compounds (1 and 2) showed cytotoxic activity against P-388 murine leukemia cells with IC50 values of 23.96 and 8.14 mM, respectively.DOI:http://dx.doi.org/10.15408/jkv.v4i1.7065